IMPLEMENTATION OF A PROGRAMME OF PILATES EXERCISES IN SOIL IN PARKINSONIAN (Fiep Bulletin - online, 2014)
Parkinson's disease (PD) is a neurodegenerative disease affecting the substantia nigra, affecting the production of the neurotransmitter dopamine, damaging the modulation of movement. The disease is characterized by bradykinesia, hypokinesia, rigidity, resting tremor, postural instability and in some cases affects cognition. The prevalence is higher in older people and males. The present study shows the functional changes of PD and discusses the Pilates method, intending to analyze the effects of this method on the ground in flexibility, quality of life , strength and balance in PD. The study was composed of 7 individuals with PD, which underwent a review before and after the implementation of a program of Pilates exercises on the ground. The questionnaires wer: MMSE, Internships Modified Hoehn and Yahr and PDQ -39. The tests applied were: TUG, time 360°, sit and reach, elbow flexion in 30 seconds, up from a chair in 30 seconds and one foot. The study proved to be very effective in implementing the Pilates method in PD, obtaining significant statistical results as strength and flexibility, as well as to balance the benefits and quality of life.
Keywords: Parkinson's Disease; Exercise; Flexibility; Strength.